Предмет: Математика,
автор: theaidgirl
3(x-8)/5+7(x+5)/6=4(7x+1,5)/15+1/3. второе
Приложения:
![](https://files.topotvet.com/i/4d8/4d8503f10fa0734815460bc30af56006.jpg)
Ответы
Автор ответа:
0
Приводим обе части уравнения к общему знаменателю 30
6 * 3(х-8) + 5 * 7(х+5) = 2 * 4(7х+1,5) + 10 * 1
18х - 144 + 35х + 175 = 56х + 12 + 10
18х + 35х - 56х = 12 + 10 + 144 - 175
- 3х = - 9
х = - 9 : (-3)
х = 3
6 * 3(х-8) + 5 * 7(х+5) = 2 * 4(7х+1,5) + 10 * 1
18х - 144 + 35х + 175 = 56х + 12 + 10
18х + 35х - 56х = 12 + 10 + 144 - 175
- 3х = - 9
х = - 9 : (-3)
х = 3
Похожие вопросы
Предмет: Алгебра,
автор: kamilllababaeva
Предмет: Английский язык,
автор: ksenia0369
Предмет: Русский язык,
автор: nikitosgordienko2010
Предмет: Математика,
автор: ророророрлр
Предмет: Математика,
автор: lesa21